2007
DOI: 10.1182/blood-2007-05-090514
|View full text |Cite
|
Sign up to set email alerts
|

A role for the MLL fusion partner ENL in transcriptional elongation and chromatin modification

Abstract: IntroductionHematopoietic development is controlled by an intricate network of finely tuned transcriptional programs. Consequently, a perturbation of the transcription factors involved can block differentiation. This developmental roadblock cooperates with mutations in pathways that signal growth and/or survival to cause acute leukemias. 1 A prime example for such a mechanism is mixed lineage leukemia. In this disease, the gene for the histone methyltransferase MLL participates in chromosomal translocations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
374
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(388 citation statements)
references
References 35 publications
8
374
0
4
Order By: Relevance
“…For example, direct binding interactions have already been described between AFF1, MLLT3 and MLLT1, and AFF1/ MLLT10, which have a functional role in leukemogenesis. 54,55 The complex of these proteins, which is called the MLLT1/ENLassociated protein complex (EAP), 55 was also linked to DOT1L, which methylates H3K79, 56 and pTEFb, which is necessary to convert 'promotor-arrested' RNA polymerase-II into an 'elongating' RNA polymerase-II. 57 In addition, it has been shown that MLLT10 binds to DOT1L and that binding of DOT1L was necessary for the transforming activity of MLL-MLLT10.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 99%
“…For example, direct binding interactions have already been described between AFF1, MLLT3 and MLLT1, and AFF1/ MLLT10, which have a functional role in leukemogenesis. 54,55 The complex of these proteins, which is called the MLLT1/ENLassociated protein complex (EAP), 55 was also linked to DOT1L, which methylates H3K79, 56 and pTEFb, which is necessary to convert 'promotor-arrested' RNA polymerase-II into an 'elongating' RNA polymerase-II. 57 In addition, it has been shown that MLLT10 binds to DOT1L and that binding of DOT1L was necessary for the transforming activity of MLL-MLLT10.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 99%
“…83,84 DOT1L binds the leukemogenic MLL-AF10 and MLL-ENL fusion proteins and indirect evidence suggests that DOT1L catalytic activity is required for transformation by these fusions. 85,86 Furthermore, DOT1L is found in nuclear complexes with AF10, ENL, and other MLL translocation partners AF4 and AF9. 85,[87][88][89][90] Ectopically expressed MLL-AF10, or a synthetic, not naturally occurring MLL-DOT1 fusion, was shown to localize to the HOXA9 locus and increase K79 methylation.…”
Section: H3k79mentioning
confidence: 99%
“…85,86 Furthermore, DOT1L is found in nuclear complexes with AF10, ENL, and other MLL translocation partners AF4 and AF9. 85,[87][88][89][90] Ectopically expressed MLL-AF10, or a synthetic, not naturally occurring MLL-DOT1 fusion, was shown to localize to the HOXA9 locus and increase K79 methylation. This corresponded to increased HOXA9 expression, consistent with the notion that H3K79 methylation is an activating chromatin modification.…”
Section: H3k79mentioning
confidence: 99%
“…In the context of the MLL-r-associated fusion proteins, MLL loses its catalytic domain. However, a unifying feature of many of the common MLL fusion partner proteins is the ability to bind to another HMT known as DOT1L (Okada et al, 2005;Bitoun et al, 2007;Mueller et al, 2007;Mohan et al, 2010;Park et al, 2010;Yokoyama et al, 2010;Biswas et al, 2011). In this manner, DOT1L is recruited to gene locations normally under the control of MLL (Okada et al, 2005;Mueller et al, 2007;Monroe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, a unifying feature of many of the common MLL fusion partner proteins is the ability to bind to another HMT known as DOT1L (Okada et al, 2005;Bitoun et al, 2007;Mueller et al, 2007;Mohan et al, 2010;Park et al, 2010;Yokoyama et al, 2010;Biswas et al, 2011). In this manner, DOT1L is recruited to gene locations normally under the control of MLL (Okada et al, 2005;Mueller et al, 2007;Monroe et al, 2011). DOT1L catalyzes the specific methylation of histone H3 at lysine 79 (H3K79), and this site-specific marking of histone H3 leads to transcriptional activation (Milne et al, 2005;Okada et al, 2005;Guenther et al, 2008;Krivtsov et al, 2008;Mueller et al, 2009;Thiel et al, 2010;Monroe et al, 2011;Nguyen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%